Techniques and Analysis for Mixed-criticality Scheduling with Mode-dependent Server Execution Budgets - Ali Awan, Muhammad (2019)
This article appears as part of the ESWEEK-TECS special issue and was presented at the International Conference on Embedded Software (EMSOFT) 2019.